Post-pandemic learning design and modern didactics (Journal of Educational Sciences, 2022)
The ubiquitous distance learning, the widespread use of digital educational technologies and online formats during the pandemic have actualized the issues of modification in the modern learning  design. During distance learning, students have adapted to independent work, have mastered the ways of learning through information resources, the attitude to the organization of pedagogical activity and relationships in the classroom is changing.  It is noted in the article that these processes require a rethinking of approaches to the projecting and design of educational programs, a revision of the content and methods of teaching in accordance with learning in the digital space. The construction of a model of a new teaching design consisting of a system of goals, content, methods and means of teaching with the active use of digital resources based on the integration of traditional and digital didactics determines the scientific significance of research work. The article substantiates methodological approaches and principles of integration of traditional didactics with digital didactics as the basis for projecting modern  learning design . In addition, the possibility of developing learning design which provides the transformation of the content and structure of educational programs for the systematic implementation of online tools in the blended learning process  is substantiated. The practical significance of the work is to determine the methods of interactive learning of students in a digital environment, the development of skills of joint  team learning. During the research of the study, using of distance learning tools and resources, ways of feedback and interactive online lessons and designing students' were  analyzed and independent work were determined.In conclusion the possibilities of integrating traditional and digital didactics in the development of modern learning design are described.Keywords: learning design, digital didactics, modern didactics, integration, blended learning and online learning